FAKTOR - FAKTOR YANG MEMPENGARUHI PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN WISATA MANGROVE DI DESA PENGUDANG KABUPATEN BINTAN - Silvani, Tantri; Haidawati; Fitria Ulfah (MarIslands, 2024)
Pengudang Village is a tourist village located in Bintan Regency. The main tourist attraction in Pengudang Village is mangrove tourism. Mangrove tourism has its own charm for tourists, especially foreign tourists. Mangroves in Pengudang Village are very beautiful and their habitats are maintained, this cannot be separated from the participation of the community because their management is community-based. The importance of community participation in supporting the development of mangrove tourism, because effective development requires involvement (participation) from various parties (stakeholders), especially the community. Therefore, researchers are interested in researching "Factors Influencing Community Participation in Tourism Development in Pengudang Village Bintan RegencyÃ¢â‚¬Â The purpose of this research is to find out the driving factors and inhibiting factors for community participation in the development of mangrove tourism in Pengudang Village. The tools and materials used in the research are laptops, stationery, questionnaires, microsoft word software. The research uses qualitative research methods. Determination of the sample is 10% of the total population of 364 people, then the total sample is 36 people and 2 key informants. The results of the study, namely the factors that influence